Developmental Anomalies in Tooth Number: An Educational Case Series of Hyperdontia and Hypodontia - Arandi, Naji (Brazilian Journal of Case Reports, 2026)
Developmental anomalies in tooth number, including anodontia, hypodontia and hyperdontia, may affect eruption, occlusion, function, and aesthetics. This case series presents eight patients with developmental tooth number anomalies encountered in clinical practice, including a maxillary paramolar, bilateral agenesis of mandibular second premolars with retained primary molars, bilateral agenesis of maxillary lateral incisors, a mesiodens associated with delayed eruption, a supplemental maxillary lateral incisor, nonsyndromic hypodontia involving five permanent teeth, nonsyndromic oligodontia involving six permanent teeth, and hypodontia involving the maxillary lateral and mandibular central incisors. Diagnoses were established through clinical and radiographic examinations, and management ranged from observation and periodic follow-up to surgical extraction, orthodontic intervention, and multidisciplinary restorative planning. These cases illustrate the diverse clinical presentations and treatment considerations associated with tooth number anomalies and underscore the importance of comprehensive clinical and radiographic evaluation for accurate diagnosis and individualized management. Collaboration among dental specialties is often required to achieve favorable functional and aesthetic outcomes.